Changes in Caries Risk in a Practice-Based Randomized Controlled Trial. (February 2018) - Rechmann, P.; Chaffee, B.W.; Rechmann, B.M.T.; Featherstone, J.D.B.
To demonstrate that Caries Management by Risk Assessment (CAMBRA) can be successfully implemented in dental practice, 30 dentists were recruited to perform a 2-y CAMBRA trial. Twenty-one dentists (18 private practices, 3 community clinics) participated in a randomized, controlled, parallel-arm, double-blind clinical trial with individual-level assignment of 460 participants to standard of care (control) versus active CAMBRA treatment (intervention). Control or active antimicrobial and remineralizing agents were dispensed at baseline and 6-, 12-, 18-, and 24-mo recall visits according to risk level and assigned treatment arm. Primary outcome measure was dentist-determined caries risk level at recall. Among initially high-risk participants, secondary outcomes were recorded disease indicators. Generalized estimating equations were used to fit log-linear models for each outcome while accounting for repeated measurements. At 24 mo, follow-up rates were 34.3% for high-risk participants (32.1% intervention, 37.1% control) and 44.2% for low-risk participants (38.7% intervention, 49.5% control). Among 242 participants classified as high caries risk at baseline (137 intervention, 105 control), a lower percentage of participants remained at high risk in the intervention group (statistically significant at all time points). At 24 mo, 25% in the intervention group and 54% in the control group remained at high risk ( P = 0.003). Among 192 participants initially classified as low risk (93 intervention, 99 control), most participants remained at low risk. At 24 mo, 89% in the intervention group and 71% in the control group were low caries risk ( P = 0.18). The percentage of initially high-risk participants with recorded disease indicators decreased over time in both intervention and control groups, being always lower for the intervention group (statistically significant at the 12- and 18-mo time point). In this practice-based clinical trial, a significantly greater percentage of high-caries-risk participants were classified at a lower risk level after CAMBRA preventive therapies were provided. Most participants initially assessed at low caries risk stayed at low risk (ClinicalTrials.gov NCT01176396).